Posterior Cloacal Variant with Clitorolabial Transposition and a Rectoperineal Fistula - Niveshni Maistry; Giulia Brisighelli; Chris Westgarth-Taylor (Georg Thieme Verlag KG, 2021)
We present a case and discuss the management of a posterior cloacal variant not as yet described in the literature. A 5-week-old infant presented to our institution with a posterior cloacal variant and transposition of the clitoris and labia. After initial radiological investigations, staged operative intervention was performed over a 1-year period. This included an initial laparotomy (with drainage of hydrocolpos and formation of a colostomy), a left ureteric reimplantation and a posterior sagittal anorectoplasty due to a rectoperineal fistula. The child is under continued long-term follow-up by our specialist pediatric surgical team.